1989
DOI: 10.1023/a:1015938522673
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The objective of this study was to develop an in vitro method to investigate the effect of ultrasound on the in vitro absorption of ibuprofen from a propylene glycol/water vehicle through human epidermis. A diffusion cell was modified so ultrasound could be applied to the vehicle and skin. Since ultrasound can increase the temperature underneath the area of application, control representing temperature effects ran concurrently to the ultrasound experiment. The results demonstrate that ultrasound can increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Synthesis of Lactam N-Acetic Acid EsterssThe 5-and 6-membered lactams (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) were prepared with acetate esters at the 1-position (Table 1). The bromoacetate esters were prepared by reaction of the appropriate alcohol with bromoacetyl bromide, and this crude bromoacetate ester was used to alkylate the sodium salt of the various lactams.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of Lactam N-Acetic Acid EsterssThe 5-and 6-membered lactams (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) were prepared with acetate esters at the 1-position (Table 1). The bromoacetate esters were prepared by reaction of the appropriate alcohol with bromoacetyl bromide, and this crude bromoacetate ester was used to alkylate the sodium salt of the various lactams.…”
Section: Methodsmentioning
confidence: 99%
“…Many methods have been used to decrease skin resistance to the passage of drugs. These include the prodrug approach, 2 iontophoresis, 3 phonophoresis, 4 and dermal penetration enhancers. 5 This last approach is most convenient; however, these compounds must be highly effective, show no irritancy or toxicity, and be stable and pharmacologically inert.…”
mentioning
confidence: 99%
“…[11] Simonin also demonstrated, using a theoretical analysis, that convective reduction of the boundary layer above the skin by stirring of the donor compartment could decrease the overall resistance of the membrane by about 10%. [68] Convection has also been cited as a possible mechanism in other HFS studies,[91] while it has not been implicated in several others. [6, 12, 92, 93]…”
Section: Mechanisms Of Skin Permeability Enhancement In Sonophoresismentioning
confidence: 99%
“…[5, 11, 92] Conversely, and not surprisingly, in studies that observed much larger temperature increases (in excess of 10 °C), thermal effects were found to play a role in increasing permeant transport, although a temperature increase alone could not explain the full enhancement observed with the HFS treatment (1 MHz, 1 W/cm 2 ). [91] Meidan et al even concluded that heating is the main mechanism of action with HFS. [87] A study of sonophoresis, at an intermediate frequency of 150 kHz (2 W/cm 2 ), also concluded that thermal effects may be a significant mechanism of increased flux of hydrophilic permeants.…”
Section: Mechanisms Of Skin Permeability Enhancement In Sonophoresismentioning
confidence: 99%
“…Phonophoresis is the use of ultrasound to enhance percutaneous absorption of a drug (15)(16)(17)(18). Phonophoresis provides an advantage as it bypasses the hepatic first-pass metabolism and avoids the side effects in absorption that occur with oral administration (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%